Impact on Growth Performance, Carcass Quality, and Physiological Characteristics of Broiler Chickens by Using the Various Levels of Dried Tarragon (Artemisia dracunculus) - Shawkat, Sarood Samal (Sulaimani Journal for Pure and Applied Sciences, 2023)
The goal of this investigation is to determine whether adding tarragon to broiler chickens 'diet affects their performance, carcass, and physiological characteristics. A total of Oneday-old two hundred eighty broiler chicks (Ross 308) broilers were used to divide randomly into 4 treatments and 5 replicates per procedure.14 birds were used at each repeat. Experimental groups only earned a base diet (control) (T1), a base diet (100 kg) + 200gm dried tarragon (T2), a base diet (100 kg) + 400gm dried tarragon (T3) and base diet (100 kg) + 600gm dried tarragon (T4). The additive of different levels of dried Tarragon not significant differences between all treatments on performances, except for relative (FCR) feed conversion rate was significantly different (p≥0.05). Although the tarragon ingredient is advantageous on the values of live body weight, body weight gain, feed intake, and FCR in overall periods (1- 42 days), that was a result of T3 therapy. The effects of treatments were significant improvement (p≥0.05) in the Production Index (PI) and Economic Figure (EF) in T3. In male broiler except for relative thigh, dramatics, and food %, different dried tarragon amounts had no discernible impact on other carcass characteristics, while in female broiler the carcass was significantly affected (p>0.05) by treatments except for relative dramatics and wings %. On the other hand, in both sexes had no impact on the values of the liver, heart and abdominal fat %, while gizzard % was significantly affected (p>0.05) in a female broiler. Therefore, bursae of fabricius in both sexes, pancreas in females, and spleen % in males were not significantly affected. Besides, the dried tarragon did not have any adverse effects on chickens 'welfare.
Keywords: Broiler; Tarragon; Performance; Carcass